Artificial Intelligence in Preserving Traditional Values and Driving Modernization: A Case Study of Pendapa Javanologi Universitas Sebelas Maret - Maram Taher; Dwi Susanto (Javanologi: International Journal of Javanese Studies, 2025)
This paper explores the role of Artificial Intelligence (AI) in balancing traditional values and modernization in Indonesian society, with a case study of the Pendapa Javanologi at Universitas Sebelas Maret. It highlights the cultural significance of traditional heritage, which remains vital to national identity amid accelerating technological advancement. This study investigates how AI can be integrated into cultural institutions to preserve local traditions while promoting innovation. Using a qualitative method, combining field observation, interviews, and document analysis, the research seeks to answer: How can AI technologies be used to safeguard cultural heritage without hindering modernization? The Pendapa Javanologi serves as an example of community-based cultural preservation, particularly in educating younger generations about Javanese traditions. This study examines how AI enhances cultural engagement through digital platforms, archives intangible assets, and supports cultural transmission. Simultaneously, the paper addresses AI's transformative impact on modernization, including improved efficiency and innovation in various sectors, while acknowledging key challenges such as implementation costs, data ethics, and human resource gaps. With Indonesia’s AI regulatory framework still evolving, the research stresses the importance of synergy among policymakers, educators, and industry to shape inclusive AI governance. Community-driven approaches, such as those practiced at Pendapa Javanologi demonstrate how technology and tradition can coexist. Strategically applied, AI offers Indonesia a path to sustainable development that respects cultural identity while embracing future innovation